Atomic density at high-angle grain boundaries in tungsten - Ksenofontov, V.A.; Mazilov, A.A.; Mazilova, T.I.; Sadanov, E.V.; Sokolenko, V.I.; Voyevodin, V.N.; Dudka, O.V.; Mikhailovskij, I.M. (Вопросы атомной науки и техники, 2011)
The oscillatory features of the atomic relaxation and the phenomenon of plane coalescence on high-angle grain boundaries in tungsten are studied by the methods of molecular statics and field ion microscopy. A nonmonotonic character of the variation of the atomic density in the near-boundary region is established. The strain field normal to the boundary plane is calculated and compared with the results obtained using the embedded-atom method in the reciprocal space. It is shown that the amplitude, period, and character of damping of the oscillations near grain boundaries can be described satisfactorily in the framework of the line forces model.